Association of lifestyle modification and pharmacological adherence on blood pressure control among patients with hypertension at Kenyatta National Hospital, Kenya: a cross-sectional study - Kimani, Samuel; Mirie, Waithira; Chege, Margaret; Okube, Okubatsion Tekeste (BMJ Open, 2019)
Objective Association of lifestyle modification and pharmacological adherence among patients with hypertension attending a national referral hospital in Kenya. Design Descriptive, cross-sectional. Setting Medical wards and outpatient clinic of a national referral hospital. Participants Patients (n=229) diagnosed with primary hypertension for at least 6months. Primary outcomes Clinical makers, cholesterol levels, anthropometrics, lifestyle/dietary habits adjusted for age, gender and education; antihypertensive adherence; views on prevention of hypertension and adequacy of hypertension information. Results Ageing was associated with elevated diastolic blood pressure (BP) (p<0.05), heart rate (HR) and cholesterol. Females had higher body mass index (BMI). More males reported drinking alcohol and smoking (p<0.001), especially the highly educated. Higher BPs were observed in smokers and drinkers (p<0.05). Daily vegetables and fruits intake were linked to lower BP, HR and BMI (p<0.05). Intake of foods high in saturated fat and cholesterol were associated with raised HR (p<0.05). Respondents on antihypertensive medication, those engaged in healthy lifestyle and took their prescribed medications had lower mean BPs than those on medication only (138/85 vs 140/90). Few respondents (30.8%) considered hypertension as preventable, mainly the single and highly educated (p<0.05). Respondents (53.6%) believed they should stop taking their antihypertensive medication once hypertension is controlled. Conclusion Missed targets for BP control and hypertension-related risks are associated with ageing, female gender, fast food and animal fat intake. Alcohol and smoking is common in males associated with poor BP control. Daily vegetables and fruits intake are associated with better BP control and overall hypertension risk reduction. Observed suboptimal BP control despite pharmacological adherence suggests lifestyle modification is needed besides antihypertensive medication. Interventions should address modifiable risk factors aggravated by age and adverse lifestyles through adopting combined lifestyle modification, pharmacological adherence and tailored expert delivered hypertension related information.
© Author(s) (or their employer(s)) 2019. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.